Literacy and Disabilities in Education : How Involved Are We? (A Systematic Literature Review) - H. Husamah; Abdulkadir Rahardjanto; Dyah Worowirastri Ekowati; Lesy Luzyawati; Miza Nina Adlini (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to review, investigate, and compare various research published in Scopus-indexed journals related to the theme of literacy for disabilities so that it will contribute to the development of literacy studies for disability groups. This study used the systematic literature review method with the PRISMA 2020 model. The search was conducted in the Scopus database, inclusion-exclusion, to obtain 41 articles. Data were collected from the Scopus database tend to increase in 2019-2023. Data were analyzed using thematic analysis techniques. The study results showed that this theme (literacy and disability) has broad dimensions and involves all parties. Various aspects of literacy can be promoted for people with disabilities, although there are adjustments. Ahlgrim-Delzell is the dominant researcher, the reference, and the pivot. The disability aspect was related to education, children, and young adults. Interestingly, the theme